Conversion of Lignocellulosic Material Into Fermentable Sugars - Mohammed, Asem Hassan; Behrendt, Frank Behrendt; Methner, Frank Jürgen (Al-Khwarizmi Engineering Journal, 2017)
Enzymatic hydrolysis process of lignocellulosic biomass materials is difficult because of inherent structural features of biomass, which represents barriers that prevent complete hydrolysis; therefore, pretreatment techniques are necessary to render biomass highly digestible in enzymatic hydrolysis process. In this research, (non?) oxidative short-term lime pretreatment of willow wood was used. A weight of  11.40 g of willow wood was mixed with an excess of calcium hydroxide (0.4 g Ca(OH)2/g raw biomass) and water loading (15 g/g raw biomass). Lime pretreatment was carried out for various periods of time including 1, 2, 3.5, 5 and 6 h, with temperatures at 100, 113, 130, 147 and 1600C, and oxygen pressures as oxidativeagent (6, 9, 13.5, 17.8, 21 bar absolute). The optimization of both pretreatment and enzymatic hydrolysis were depended on the maximum overall yields of glucan and xylan after two processes of lime pretreatment and enzymatic hydrolysis. The optimal conditions of pretreatment were as follow: 1) 1.33 h, 1470C, 17.8 bar absolute, 0.26 g Ca(OH)2/g raw biomass. 2) 1.25 h, 155 0C, 21 bar absolute, 0.26 Ca(OH)2/g raw biomass. Furthermore, the optimal values for low impact factors such as water loading was 15 g/g raw biomass and particle size was less than 3 mm. The optimal conditions of enzymatic hydrolysis were as follow: Cellulase enzymeloading was 0.1 g /g glucan in raw biomass, at substrate concentration of 50 g/L during 72 h of enzymatic hydrolysis The yield of enzymatic hydrolysis under these conditions were as follow: 96.00 g glucan/100 g of glucan in raw biomass, and 65.00 g xylan/100 g xylan in raw biomass.